2017
DOI: 10.1111/jopy.12316
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Self‐Esteem Judgments at Zero Acquaintance

Abstract: Our findings show that strangers can quite accurately detect individuals' self-reported and informant-reported self-esteem when targets are observed in a public self-presentational situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Finally, we cannot preclude that the more consistent relations between momentary self-esteem and self-reported perceptions (i.e., self- and metaperceptions) compared to its link with other-perceptions of social inclusion may reflect a potential method effect, as self-esteem was also measured by self-report across both study parts. Future research could consider the use of other-reports of self-esteem (Hirschmüller et al, 2018) as an extension to avoid potential method biases arising from the exclusive use of self-reports (Podsakoff et al, 2003). At the same time, we would like to highlight that self-reported self-esteem in particular should be considered the most appropriate approach to gain insight into self-perceived levels of self-evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we cannot preclude that the more consistent relations between momentary self-esteem and self-reported perceptions (i.e., self- and metaperceptions) compared to its link with other-perceptions of social inclusion may reflect a potential method effect, as self-esteem was also measured by self-report across both study parts. Future research could consider the use of other-reports of self-esteem (Hirschmüller et al, 2018) as an extension to avoid potential method biases arising from the exclusive use of self-reports (Podsakoff et al, 2003). At the same time, we would like to highlight that self-reported self-esteem in particular should be considered the most appropriate approach to gain insight into self-perceived levels of self-evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The relevant concepts from the lens model are criterion (continuing with this example: the targets’ actual extraversion, as operationally defined), cue validities (how targets’ actual extraversion, as operationally defined, is correlated with measured aspects of the targets’ appearance or behavior—together called cues), and cue utilization (how perceivers’ ratings of the targets’ extraversion correlate with the measured cues). Published lens models address a wide range of constructs, including personality traits, psychopathy, emotions, self‐esteem, academic achievement, status, pain experience, and rapport (e.g., Bernieri, Gillis, Davis, & Grahe, ; Gosling, Ko, Mannarelli, & Morris, ; Hirschmüller, Schmukle, Krause, Back, & Egloff, in press; Laukka et al, ; Ruben & Hall, ; Sahoo & Sahoo, ; Schmid Mast & Hall, ; ten Brinke et al, ).…”
Section: Interpersonal Accuracymentioning
confidence: 99%
“…Several studies have indicated that unfamiliar laypeople are able to accurately judge others’ personality traits based on subtle cues, such as a person’s natural stream-of-consciousness essays (Holleran and Mehl, 2008), textual information explicitly covering major life domains (Borkenau et al, 2016), photos of facial expressions (Sutherland et al, 2015; Walker and Vetter, 2016), video clips of someone introducing themselves (Hirschmüller et al, 2017), and other incidental cues such as photographs of someone’s shoes (Gillath et al, 2012), information on their music preferences (Rentfrow and Gosling, 2006), and images of their bedrooms and offices (Gosling et al, 2002).…”
Section: Introductionmentioning
confidence: 99%